P120-Catenin Regulates Early Trafficking Stages of the N-Cadherin Precursor Complex - Wehrendt, Diana P.; Carmona, Fernando; González Wusener, Ana E.; González, Ángela; Martínez, Juan M. Lázaro; Arregui, Carlos O. (PLOS ONE, 2016)
It is well established that binding of p120 catenin to the cytoplasmic domain of surface cadherin prevents cadherin endocytosis and degradation, contributing to cell-cell adhesion. In the present work we show that p120 catenin bound to the N-cadherin precursor, contributes to its anterograde movement from the endoplasmic reticulum (ER) to the Golgi complex. In HeLa cells, depletion of p120 expression, or blocking its binding to N-cadherin, increased the accumulation of the precursor in the ER, while it decreased the localization of mature N-cadherin at intercellular junctions. Reconstitution experiments in p120-deficient SW48 cells with all three major isoforms of p120 (1, 3 and 4) had similar capacity to promote the processing of the N-cadherin precursor to the mature form, and its localization at cell-cell junctions. P120 catenin and protein tyrosine phosphatase PTP1B facilitated the recruitment of the N-ethylmaleimide sensitive factor (NSF), an ATPase involved in vesicular trafficking, to the N-cadherin precursor complex. Dominant negative NSF E329Q impaired N-cadherin trafficking, maturation and localization at cell-cell junctions. Our results uncover a new role for p120 catenin bound to the N-cadherin precursor ensuring its trafficking through the biosynthetic pathway towards the cell surface.